Anosmia and covid-19 in Yogyakarta, Indonesia: a case series - Rizka Fakhriani; Asti Widuri (Universitas Muhammadiyah Surabaya, 2021)
ABSTRACTCovid-19 (coronavirus disease 2019) had spread to the whole world. This kind of virus attacks the human respiratory system, and it caused death. In other words, there were many symptoms of Covid-19, which attacks the respiratory system. One of the symptoms was anosmia or smell disorder. This research might provide information about the anosmia in Covid-19 patients. This study aimed to investigate and present a series about anosmia and Covid-19 in Yogyakarta on June 2020. Three cases from three patients of RT-PCR-confirmed SARS-CoV-2-infected patients diagnosed with smell disorder were presented, starting from the symptom until the patients were getting treatments. This research also explained anosmia as one of the symptoms of Covid-19. Anosmia or losing olfactory function or smell disorder which could distract people’s healthy. Then, in this situation, it could be one of the symptoms of Covid-19. Keywords : anosmia, smell disorder, covid-19Corresponding Author : rizkafakhriani@gmail.com